2002
DOI: 10.1677/joe.0.1740225
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the beta-cell mass increase induced by chronic sucrose feeding to normal rats

Abstract: The aim of the present study was to clarify the mechanisms by which a sucrose-rich diet (SRD) produces an increase in the pancreatic -cell mass in the rat. Normal Wistar rats were fed for 30 weeks either an SRD (SRD rats; 63% wt/wt), or the same diet but with starch instead of sucrose in the same proportion (CD rats). We studied body weight, serum glucose and triacylglycerol levels, endocrine tissue and -cell mass, -cell replication rate (proliferating cell nuclear antigen; PCNA), islet neogenesis (cytokeratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
3
10
1
Order By: Relevance
“…Nevertheless, postprandial glucose and insulin levels, which were not measured, might have differed as reported previously by our group (10,11). Other investigators have also reported that sucrose and other high glycemic starch amylopectin can induce islet hypertrophy (31)(32)(33). Furthermore, amylopectin-fed rats had larger and more fibrotic islets than low glycemic-amylose-fed rats without decrease in insulin sensitivity (32).…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, postprandial glucose and insulin levels, which were not measured, might have differed as reported previously by our group (10,11). Other investigators have also reported that sucrose and other high glycemic starch amylopectin can induce islet hypertrophy (31)(32)(33). Furthermore, amylopectin-fed rats had larger and more fibrotic islets than low glycemic-amylose-fed rats without decrease in insulin sensitivity (32).…”
Section: Discussionmentioning
confidence: 56%
“…β-cells slowly divide in adult mice and rats [14], but the process can be accelerated temporarily under physiologic [15][17] or pathologic conditions [3], [5], [6]. For instance, β-cell proliferation rates increase during adolescence [18], [19], pregnancy [17], [20], dietary manipulations [15], [21] that may be further stimulated in insulin-resistant states [22] and obesity, during organ regeneration after partial pancreatectomy [7], [23], or following β-cell specific cell-ablation [6]. However, no consensus has emerged regarding the proportional roles played by β-cell mitosis or neogenesis, and what regulates such β-cell expansion in vivo [24].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, glucose stimulates β-cell proliferation in fetal and adult rat islets, in mouse islets, and in several rodent insulinoma β-cell lines (3,7,10). In vivo, glucose promotes β-cell proliferation in numerous models, including a high sucrose diet, recovery from hypoglycemia, and partial pancreatectomy (1114). Alonso et al (15) demonstrated that a 4-day intravenous infusion of 50% glucose into mice, which modestly increases blood glucose concentrations, leads to markedly increased β-cell proliferation as determined by 5-bromo-2′-deoxyuridine (BrdU) incorporation, consistent with earlier rodent infusion studies (16,17).…”
mentioning
confidence: 99%